Analys av framtida potential för virkesköp från privata skogsägare i Västerbottens län - Karlsson, Niklas (2011)
This study was conducted on behalf of SCA forest AB, Västerbottens forest administration. Timber procurement from non-industrial private forest owners has become an increasingly important part of SCA:s wood supply. The objectives of this study was to report the current forest conditions in the private forests in the county of Västerbotten, analyse the potential for procurement of wood from private forest owners, and provide a basis for decisions on future strategies for timber procurement from private owners. Material and data have been collected from different sources, mainly from Swedish National Forest Inventory and SKA-VB08. This material was the basis for the analysis and calculations performed with the Heureka application PlanWise. This study area was divided into six different analytical areas (Coastal south, Coastal middle, Lycksele, Inland south, Inland north, Skellefteå), where each area of analysis is represented by a number of municipalities. In this study, two scenarios were specified; one describing the current forest management with current harvesting levels and the effects of these assumptions, the second to illuminate what potential there is for future timber harvesting. For the second scenario, further sensitivity analysis was made to identify the areas where harvesting levels can be increased. The results show that the growing timber stock is generally increasing in each area, to a varying degree. The areas showing the greatest potential to increase harvesting levels are Lycksele and Inland south, closely followed by the Inland north and Skellefteå. For Coastal south and Coastal middle, it is not possible to increase harvest level.